Evaluation of Myostaal SB in Osteopenia Management through Bone Remineralization: A Proof-of-Concept, Open-Label, Single-Arm Study in Middle-Aged and Older Adults - Chitrakar, Mrudul; Harit, Mahesh Kumar; Chawda, Mukesh; Nalawade, Megha; Pawar, Vinay; Bhapkar, Vedvati (International Journal of Pharmaceutical Investigation, 2026)
Background Myostaal SB is a rational herbo-mineral Ayurveda formulation for management of Asthikshaya (~ osteopenia). It contains Kukkutandatvak Bhasma (Processed Hen-egg Shell), Asthisamhruta (Cissus quadrangularis), and Shatavari (Asparagus racemosus). Present proof-of-concept clinical study was planned to explore its efficacy in osteopenia management. The primary objective was to evaluate improvement of Bone Mineral Density (BMD) scores in DEXA scan. The effect on bone health biochemical markers viz., serum Alkaline Phosphatase, Parathyroid and Vitamin D were also assessed, along with clinical and quality of life improvement. Materials and Methods Total 35 adults of either sex aged, 40-75 years suffering from osteopenia with BMD T- score between -1 to -2.5 were allocated to intervention. All participants had a documented history of fractures likely resulting from low-impact trauma or injuries. Tab. Myostaal SB was given in a dose of one tablet thrice a day for 180 days. The baseline parameters, laboratory investigations were done as per the protocol. Data generated through clinical study were subjected to appropriate statistical tests. Results The results indicated significant BMD improvement in mean T-scores of AP spine and radius and marked improvement in femur and femur neck. Significant reduction in ALP and PTH; and marked improvement in Vitamin D levels were observed. Clinical improvement and improved quality of life were also noted. No adverse events were reported. Conclusion The positive role of Myostaal SB in bone remodeling was confirmed with improvement in bone strength and bone resorption markers. Thus, Myostaal SB Tablets can play a positive role in the management of osteopenia.
Keywords: Osteoporosis; Cissus quadrangularis; DEXA; Bone Health; Bone Mineral Density; BMD.